Similar fatty acid status of plasma lipids in postmenopausal women newly diagnosed with breast cancer and those receiving aromatase inhibitor therapy - Krstić, Predrag; Vučić, Vesna; Paunović, Marija; Petrović, Snježana; Nedović, Nikola; Kostić, Sanja; Arsić, Aleksandra (Vojnosanitetski pregled, 2021)
Background/Aim. Dysregulation of fatty acid (FA) metabolism is recognized as a component of malignant transformation in many cancers, including breast cancer (BC), and is often related to disease progression and prognosis. Adjuvant endocrine BC therapy using aromatase inhibitors may also influence FA metabolism. Thus, the aim of our study was to compare plasma total lipids FA status in newly diagnosed postmenopausal patients with BC and in postmenopausal women with BC receiving aromatase inhibitors at least 2 years after completing chemotherapy with healthy women. Methods. The study included 17 newly diagnosed postmenopausal BC patients (ND group) and 21 postmenopausal women with BC receiving aromatase inhibitor therapy 2 years after ending chemotherapy (AI group), while a total of 15 apparently healthy women without a family history of BC, comparable in age and body mass index, served as a control group. Results. In both patient groups, we found significantly lower levels of vaccenic acid (18:1n-7), alpha-linolenic acid (18:3n-3), gamma-linolenic acid (GLA, 18:3n-6), and docosapentaenoic acid (22:5n-3), and a significantly higher level of di-homo-gamma-linolenic (20:3n-6), when compared with the control group. On the other hand, a significantly lower level of stearic acid (18:0) was observed only in AI patients, while the level of linoleic acid (18:2n-6) was significantly higher in ND women than in the control group. Reduced estimated activities of D6 and D5 desaturases were found in both patient groups than in the control group. Conclusion. Our results indicate that FA profiles of plasma lipids of the newly diagnosed, untreated BC patients are very similar to those of cured BC patients who underwent all sessions of chemotherapy and received aromatase inhibitors for at least two years. Additionally, according to our results, their FA profiles markedly differ from those of healthy women. Therefore, supplementation with omega-3 FA and GLA could have beneficial effects in these patients, and further studies should address the potential clinical benefits of the supplementation.
Keywords: aromatase inhibitors; antineoplastic agents; breast neoplasms; fatty acids; postmenopause; women